Spatiotemporal Dynamics of Mangrove Cover Change in Tanjungpinang City, Riau Islands Province - Sudjana, Lili; Sodikin, Sodikin; Astarika, Rina (Jurnal Penelitian Geografi (JPG), 2024)
Tanjungpinang City is a coastal area surrounded by the sea and characterized by a mangrove ecosystem. Coastal regions are more dynamic and vulnerable compared to other areas, both naturally and due to human activities. This study aims to determine the rate of mangrove cover change in Tanjungpinang City from 2007 to 2023 and to predict changes in mangrove cover by the year 2035. The methodology employed involves spatiotemporal analysis of land cover change using Landsat 7 ETM+ imagery from 2007, Landsat 8 OLI imagery from 2015, and Sentinel-2A MSI imagery from 2023. The prediction for mangrove cover change in 2035 was conducted using the Land Change Modeler. The results indicate that from 2007 to 2023, there was a decrease in mangrove area of 323.40 hectares, with a rate of 20.21 hectares per year. The predicted mangrove coverage in Tanjungpinang City for the year 2035 is estimated to be 977.72 hectares, representing a reduction of 461.21 hectares (32.05%) from the coverage in 2023. Keywords: Land Change Modeler; Google Earth Engine; mangrove cover prediction; Landsat; Sentinel-2A